2018
DOI: 10.1111/ases.12617
|View full text |Cite
|
Sign up to set email alerts
|

Extent of intraluminal exfoliated malignant cells during surgery for colon cancer: Differences in cell abundance ratio between laparoscopic and open surgery

Abstract: Exfoliated malignant cells were detected at anastomosis sites in patients with colon cancer. On the distal side, laparoscopic colectomy may prevent the development of exfoliated malignant cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The second problem, the dispersal of cancer cells in the abdominal cavity, is discussed in terms of: (1) The presence of cancer cells in the anastomotic intestinal tract; and (2) the prognostic value of a positive cytological diagnosis. First, it has been previously reported that, in colon cancer, the presence of free cancer cells in the intestinal tract to be anastomosed is as high as 30%-50%[ 22 , 23 ]. It has also been reported that the positive rate is higher for open surgery than for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The second problem, the dispersal of cancer cells in the abdominal cavity, is discussed in terms of: (1) The presence of cancer cells in the anastomotic intestinal tract; and (2) the prognostic value of a positive cytological diagnosis. First, it has been previously reported that, in colon cancer, the presence of free cancer cells in the intestinal tract to be anastomosed is as high as 30%-50%[ 22 , 23 ]. It has also been reported that the positive rate is higher for open surgery than for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, exfoliated malignant cells were revealed at the site of an anastomosis during colorectal surgery, and it was suggested that the anastomotic site should be located more than 100 mm from the primary tumor. 11 Second, it is considered that this method might carry higher risks of contamination and related surgical site infections. Surgeons have to take care to prevent the spillage of intraluminal contents into the peritoneal cavity as much as possible, for example, using bowel clamping.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exfoliated malignant cells may spill during the operation and contribute to peritoneal dissemination or port site recurrence in addition to anastomotic recurrence. Previously, exfoliated malignant cells were revealed at the site of an anastomosis during colorectal surgery, and it was suggested that the anastomotic site should be located more than 100 mm from the primary tumor 11 . Second, it is considered that this method might carry higher risks of contamination and related surgical site infections.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of ICA in colorectal surgery, there were initially concerns regarding oncological outcomes. In particular, it was suggested that malignant cell dissemination may occur when opening the intestinal tract within the abdomen resulting in peritoneal recurrence through leaked contents as well as inadequate lymph node harvesting 5,6 . It has been subsequently determined that both ECA and ICA have similar rates of lymph nodes harvested and retrieved enough nodes to ensure a radical cure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was suggested that malignant cell dissemination may occur when opening the intestinal tract within the abdomen resulting in peritoneal recurrence through leaked contents as well as inadequate lymph node harvesting. 5,6 It has been subsequently determined that both ECA and ICA have similar rates of lymph nodes harvested and retrieved enough nodes to ensure a radical cure. 6 Additionally, studies have determined that there is comparable 3-and 5-year overall survival and disease-free survival between ICA and ECA in right and left hemicolectomy, with similar rates of peritoneal seeding found on follow-up.…”
mentioning
confidence: 99%